1998
DOI: 10.1002/(sici)1096-9861(19981019)400:2<197::aid-cne3>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Timing and origin of the first cortical axons to project through the corpus callosum and the subsequent emergence of callosal projection cells in mouse

Abstract: A precise knowledge of the timing and origin of the first cortical axons to project through the corpus callosum (CC) and of the subsequent emergence of callosal projection cells is essential for understanding the early ontogeny of this commissure. By using a series of mouse embryos and fetuses of the hybrid cross B6D2F2/J weighing from 0.36 g to 1.0 g (embryonic day E15.75-E17.25), we examined the spatial and temporal distribution of callosal projection cells by inserting crystals of the lipophilic dye (DiI: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 50 publications
3
58
1
Order By: Relevance
“…Cresyl violet-stained brain sections showed that the overall morphology of the telencephalon of jsap1 -/-at E14.5-E15.5 did not obviously differ from that of jsap1 +/+ (Figures 1A-1D; see also Figures 2-5). Our cresyl violet-stained brain sections revealed that jsap1 +/+ brains formed the CC during E15.5-E16.5 as reported previously (Koester and O'Leary, 1994;Ozaki and Wahlsten, 1998), while the early axons of the CC in the jsap1 -/-brain at E15.5-E16.5, at least in part, crossed the midline ( Figures 1C-1F). In jsap1 +/+ brains at E17.5, the axon bundle of the CC became thicker and formed a typical U-shaped tract, whereas in jsap1 -/-brains, late arriving neocortical-originated callosal axons failed to cross the midline.…”
Section: Temporal Patterns Of Developmental Defects Of the Telencephasupporting
confidence: 85%
See 1 more Smart Citation
“…Cresyl violet-stained brain sections showed that the overall morphology of the telencephalon of jsap1 -/-at E14.5-E15.5 did not obviously differ from that of jsap1 +/+ (Figures 1A-1D; see also Figures 2-5). Our cresyl violet-stained brain sections revealed that jsap1 +/+ brains formed the CC during E15.5-E16.5 as reported previously (Koester and O'Leary, 1994;Ozaki and Wahlsten, 1998), while the early axons of the CC in the jsap1 -/-brain at E15.5-E16.5, at least in part, crossed the midline ( Figures 1C-1F). In jsap1 +/+ brains at E17.5, the axon bundle of the CC became thicker and formed a typical U-shaped tract, whereas in jsap1 -/-brains, late arriving neocortical-originated callosal axons failed to cross the midline.…”
Section: Temporal Patterns Of Developmental Defects Of the Telencephasupporting
confidence: 85%
“…In the current study, we investigated the temporal patterns of the developmental defects during the early development of jsap1 -/-brains. Previous studies reported that the early axonal extension of the CC, which stems from the cingulate cortex, pioneers across the midline of the telencephalon during E15.5-E16.5, and subsequently the late arriving collaterals originating from other regions of the neocortex join the existing tract (Koester and O'Leary, 1994;Ozaki and Wahlsten, 1998;Rash and Richards, 2001). Cresyl violet-stained brain sections showed that the overall morphology of the telencephalon of jsap1 -/-at E14.5-E15.5 did not obviously differ from that of jsap1 +/+ (Figures 1A-1D; see also Figures 2-5).…”
Section: Temporal Patterns Of Developmental Defects Of the Telencephamentioning
confidence: 99%
“…However, a recent study suggested that the cingulate axons do not pioneer the corpus callosum and instead project to the contralateral hippocampus (68). This study also suggested that the pioneering neurons for the corpus callosum were located in the rostrolateral neocortex.…”
Section: Pioneering Axons In the Development Of The Corpus Callosummentioning
confidence: 66%
“…The cingulate cortex sends the first axons across the cortical midline (67,68) at E17 in the rat and E15.5 in the mouse. However, a recent study suggested that the cingulate axons do not pioneer the corpus callosum and instead project to the contralateral hippocampus (68).…”
Section: Pioneering Axons In the Development Of The Corpus Callosummentioning
confidence: 99%
See 1 more Smart Citation